Ring width chronolgies (N=181) from seven boreal forest tree species and shrubs (willows) across a bioclimatic gradient in Alaska sampled in 2023 - Stefan Kruse; Sarah Haupt; Linfeng Wei (PANGAEA, 2025)
The data set consists of tree ring width chronologies from tree species. The samples were taken with an increment borer predominantly from the north of the tree at breast height (1.3 m above ground) and were dried in the field. In Potsdam, we sanded, digitized and further processed the scans by identifying the ring layers (from bark to pith and including or estimating the centre) and exporting the tree ring width for each year in one data file. By crossdating we checked against other tree ring width chronologies from the same site for missing rings and corrected them. The data containing files in dendrochronological TUCSON format (1/100 mm) are added in the Metadata-section as "other version". The region covered is part of the Northern Boreal Forest and the Tundra-Taiga Ecotone (TTE). The fieldwork was planned and carried out by researchers from the Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research (AWI) and the University of Alaska Fairbanks (UAF). It took place in the summer of 2023, from 20 June to 19 July. The study area covers boreal forests in different bio-climatic regions from the northern tundra and open forested areas in the Brooks Range. It contains sites in Alaska Interior and the southern region of the boreal mainland of Alaska following generally all major roadways.